Analysis of the Influence of Seafarers' Competencies on Salaries in the Indonesian Shipping Industry - Nalle, Carles Yerid Absalom; Sumarta, Ryan Puby (International Journal of Science and Society, 2024)
The international shipping industry is the backbone of global trade, with around 90% of international trade carried out by sea. As an integral part of the global transportation system, this industry plays an important role in facilitating the exchange of goods and services between countries. In this context, the quality and competence of seafarers is a crucial factor in ensuring the safety and efficiency of ship operations. This research explores the influence of Certificate of Competency (COC) and Certificate of Proficiency (COP) diplomas on seafarers' salaries in Indonesia, a developing country with unique maritime industry characteristics. Using a quantitative approach, this research analyzed data from 49 seafarers, and found that COC had a significant positive influence on wages, while COP did not show a statistically significant influence. These findings emphasize the importance of COC certification in increasing seafarers' earning potential, and suggest that the focus of seafarers' career development be directed at achieving higher COC levels for career advancement in the maritime industry.